Consciousness and 4M man matter mind meditation [2vol. set] ramblings of a man in life nature and love of God - Anjaneyulu, T. S. S. (Lucknow Grey Parrot, 2017)
What is the purpose of human existence and where does humanity figure exactly in the universe? Answers to these questions have been sought from time to time. Ancient holistic knowledge answers us that there is no other thing except universal consciousness which is everything. Modern science is coming to the understanding that everything in the universe including human life is a part of a larger design of cosmic order. Life is much more beyond learning, earning and enjoying. It is also beauty, music and values, love, compassion and sacrifice. These aspects have been highlighted in the book. It attempts to present both the matter and the spirit in harmony in all aspects of human life and activity. The book has twenty chapters in two volumes, first volume has12 chapters and the second of 8 chapters. The first volume presents largely the material aspects of human life and man's relation to nature and the subtle aspects, prana, faith, truth and humanism, creativity, aesthetics - painting, music and dance in brief. The second volume is largely devoted to non material aspects - consciousness, wholeness, light and reality wisdom and sheaths covering reality. It presents correspondence between material science and ancient wisdom through statements from the Upanishads and Gita and other aspects of word, mantra, yantra, tantra, yoga and concludes with meditation.
Keywords: Consciousness mental process; Consciousness meditation